Being left at the altar: A content analysis of the Ports of Houston and Galveston merger case that never happened. (March 2018) - Galvao, Cassia Bomer; Gharehgozli, Amir; Mileski, Joan
Abstract: Previous literature has focused on the economic drivers of efficiency to enhance port cooperation. This paper examines under which conditions port cooperation is successful or unsuccessful through a management lens using Axelrod's theory of the evolution of cooperation. Using content analysis methodology, we explore the case of the year 2001 failed merger of the Ports of Houston and Port of Galveston which continues to plague business between these two ports. We find that port characteristics drive port cooperation not merely economic efficiency. The characteristics that enhance cooperation include direct competition between the potential cooperating ports, similar size of each and economic rationality in the decision making to merge rather than political or social drivers. Further, we see that non-cooperation or a failed merger is not necessarily a bad result for each port. The failure may force each port to behave more strategically, which can enhance performance. In the case of the Ports of Houston and Port of Galveston, the failed merger serves as a wake-up call to differentiate the mix of customers served.